Masters Athlete Screening Study (MASS): incidence of cardiovascular disease and major adverse cardiac events over five years of screening. (14th October 2021) - Morrison, B N; Isserow, S; MacDonald, M; Cater, C; Zwaiman, I; Taunton, J; Warburton, D E R; McKinney, J
Abstract: Background: The long-term implications of cardiovascular disease (CVD) in masters athletes, and whether screening decreases their risk of major adverse cardiac events (MACE) is unknown. Purpose: To evaluate the incidence of CVD and MACE over five years of a screening study. Methods: Masters athletes (≥35 years) from a variety of sports without previous history of coronary artery disease (CAD) underwent yearly cardiovascular screening. The screen consisted of anthropometrics, blood pressure, resting electrocardiogram, modified American Heart Association 14-element recommendations, cardiovascular event questionnaire, physical examination (year 1) and Framingham Risk Score (years 1–3). Participants with an abnormal screen according to the European Association of Cardiovascular Prevention and Canadian Cardiology Society Guidelines underwent further evaluations (computed coronary tomography angiography was not included for all athletes but based on clinical assessment). Participants who withdrew during the study received a follow-up questionnaire to determine MACE and vital status. Results: In the first year of the Masters Athlete Screening Study, 798 masters athletes (62.7% male, 54.6±9.5 years) were screened; 91 (11.4%) of the cohort were found to have CVD. CAD was the most common diagnosis (69.2%). During the following four years, there were an additional 89 CVD diagnoses with an incidence rate of 3.58/100, 4.14/100, 3.74/100, 1.19/100, for years two to five, respectively. Fifteen participants had more than one diagnosis. The most common diagnoses over the five years were arrhythmias (n=33; 37.1%), aortic dilatation (n=20; 22.5%), CAD (n=18; 20.2% (5 obstructive, 13 non-obstructive)) and other (n=7; 7.9%) (myocarditis (n=2), myocardial bridging (n=1), cerebrovascular disease (n=1), dilated cardiomyopathy (n=1), probable Long QT syndrome (n=1), papillary fibroelastoma (n=1)). A total of 10 MACE occurred (two cardiovascular deaths, five myocardial infarctions and three cerebrovascular accidents). All events occurred in male athletes (63.6±12.5 years). Out of the 136 participants that received the lost to follow-up questionnaire, 101 (74.3%) completed it. Of those, one male athlete underwent percutaneous coronary intervention. The incidence of MACE over the study period was 0.30/100 athletes per year. Conclusion: Yearly cardiovascular screening of masters athletes identified ∼3 new diagnoses per 100 athletes per year. Ten MACE occurred despite yearly screening and high CV fitness of masters athletes. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): MITACs and CIHR